Genetic Link Determining the Maternal-Fetal Circulation of Vitamin D - Sampathkumar, Aparna; Tan, Karen M.; Chen, Li; Chong, Mary F. F.; Yap, Fabian; Godfrey, Keith M.; Chong, Yap Seng; Gluckman, Peter D.; Ramasamy, Adaikalavan; Karnani, Neerja (Frontiers in Genetics, 2021)
Vitamin D is an essential micronutrient whose demand is heightened during pregnancy to support the growth of the fetus. Furthermore, the fetus does not produce vitamin D and hence relies exclusively on the supply of maternal vitamin D through the placenta. Vitamin D inadequacy is linked with pregnancy complications and adverse infant outcomes. Hence, early predictive markers of vitamin D inadequacy such as genetic vulnerability are important to both mother and offspring. In this multi-ethnic Asian birth cohort study, we report the first genome-wide association analysis (GWAS) of maternal and fetal vitamin D in circulation. For this, 25-hydroxyvitamin D (25OHD) was measured in the antenatal blood of mothers during mid gestation (n=942), and the cord blood of their offspring at birth (n=812). Around 7 million single nucleotide polymorphisms (SNPs) were regressed against 25OHD concentrations to identify genetic risk variants. About 41% of mothers had inadequate 25OHD (≤75nmol/L) during pregnancy. Antenatal 25OHD was associated with ethnicity [Malay (Β=−22.32nmol/L, p=2.3×10−26); Indian (Β=−21.85, p=3.1×10−21); reference Chinese], age (Β=0.47/year, p=0.0058), and supplement intake (Β=16.47, p=2.4×10−13). Cord blood 25OHD highly correlated with antenatal vitamin D (r=0.75) and was associated with ethnicity [Malay (Β=−4.44, p=2.2×10−7); Indian (Β=−1.99, p=0.038); reference Chinese]. GWAS analysis identified rs4588, a missense variant in the group-specific component (GC) gene encoding vitamin D binding protein (VDBP), and its defining haplotype, as a risk factor for low antenatal (Β=−8.56/T-allele, p=1.0×10−9) and cord blood vitamin D (Β=−3.22/T-allele, p=1.0×10−8) in all three ethnicities. We also discovered a novel association in a SNP downstream of CYP2J2 (rs10789082), a gene involved in 25-hydroxylation of vitamin D, with vitamin D in pregnant women (Β=−7.68/G-allele, p=1.5×10−8), but not their offspring. As the prevention and early detection of suboptimal vitamin D levels are of profound importance to both mother and offspring’s health, the genetic risk variants identified in this study allow risk assessment and precision in early intervention of vitamin D deficiency.